Recognition or Misrecognition? Investigating State Recognition, Structural Discrimination and the Struggle of Sunda Wiwitan in Indonesia - Rakhmat Hidayat (Muslim Politics Review, 2026)
This paper investigates the politics behind recognition of freedom of religion or belief (FoRB) in Indonesia by examining the lived experiences of the indigenous Sunda Wiwitan community. The study highlights a persistent contradiction between constitutional guarantees of religious freedom and the continuing dominance of state-recognized religions within Indonesia’s legal and administrative systems. As a result, indigenous belief communities continue to face structural obstacles in accessing civil rights, education, religious services, and equal citizenship. These conditions demonstrate that FoRB is not solely an issue of individual rights violations, but also a broader problem of institutional recognition embedded in state regulations, public policies, and everyday social relations. This paper employs Nancy Fraser’s theoretical framework by emphasizing the concepts of misrecognition and maldistribution to examine the structural inequalities experienced by indigenous believers. The study analyzes how indigenous belief communities, particularly followers of Sunda Wiwitan, face not only cultural and institutional denial of equal status, but also unequal access to civil rights, public services, and social participation. Through this perspective, exclusion is understood as both a symbolic and material form of injustice embedded within state and societal structures. Using a qualitative ethnographic approach, this research is based on long-term fieldwork conducted from 2017 to 2024 in several Sunda Wiwitan communities in West Java through participant observation, in-depth interviews, and document analysis. The findings reveal that FoRB in Indonesia remains strongly influenced by an “official religion paradigm,” limiting substantive equality and social inclusion despite a key 2017 Constitutional Court ruling acknowledging indigenous beliefs.